2016
DOI: 10.1186/s12917-016-0875-5
|View full text |Cite
|
Sign up to set email alerts
|

Recombinase polymerase amplification assay for rapid detection of lumpy skin disease virus

Abstract: BackgroundLumpy skin disease virus (LSDV) is a Capripoxvirus infecting cattle and Buffalos. Lumpy skin disease (LSD) leads to significant economic losses due to hide damage, reduction of milk production, mastitis, infertility and mortalities (10 %). Early detection of the virus is crucial to start appropriate outbreak control measures. Veterinarians rely on the presence of the characteristic clinical signs of LSD. Laboratory diagnostics including virus isolation, sequencing and real-time polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Lumpy skin disease (LSD) mainly infects cattle and is characterized by fever, lymphadenitis, edema of subcutaneous cellular tissue and viscera, cutaneous nodules (lumps), ocular discharge, and inflammation of the mucosae (Prozesky and Barnard 1982 ). It is a transmissible disease that is transferred by various arthropods (Chihota et al 2003 ) and causes significant economic losses because of cattle exhaustion, hide damage, infertility, mastitis, and reduced milk production and up to 20% mortality is reported (Shalaby et al 2016 ). LSD has been reported in other domestic species and wildlife naturally and through experimental infection (Young et al 1970 ; Usadov et al 2018 ; EFSA (European Food Safety Authority).…”
Section: Introductionmentioning
confidence: 99%
“…Lumpy skin disease (LSD) mainly infects cattle and is characterized by fever, lymphadenitis, edema of subcutaneous cellular tissue and viscera, cutaneous nodules (lumps), ocular discharge, and inflammation of the mucosae (Prozesky and Barnard 1982 ). It is a transmissible disease that is transferred by various arthropods (Chihota et al 2003 ) and causes significant economic losses because of cattle exhaustion, hide damage, infertility, mastitis, and reduced milk production and up to 20% mortality is reported (Shalaby et al 2016 ). LSD has been reported in other domestic species and wildlife naturally and through experimental infection (Young et al 1970 ; Usadov et al 2018 ; EFSA (European Food Safety Authority).…”
Section: Introductionmentioning
confidence: 99%
“…The quick and uncomplicated setup can be easily integrated into existing monitoring protocols and may also provide diagnostic options for other important pathogens in zoological institutions. RPA has been adopted for other emerging and neglected infectious diseases [ 42 , 43 , 44 , 45 , 46 ]. Negative RPA results in our study were confirmed by negative results in real-time IS900 PCR.…”
Section: Discussionmentioning
confidence: 99%
“…However, the above methods have been either too time-consuming or require high-precision instruments to meet practical needs [ 19 , 20 ]. RPA isothermal amplification techniques can amplify nucleic acids and detect the products without a requirement of special instrument or complex operations [ 21 24 ]. It is worth mentioning that human body heat can indeed incubate RPA reactions under certain limit resources [ 25 ].…”
Section: Discussionmentioning
confidence: 99%